PENGARUH PEMBERIAN PUPUK KOMPOS TERHADAP PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus) - Etivera Safuf; Alfonsius Thomas; Johan A. Rombang; Josephus I. Kalangi (COCOS, 2015)
ABSTRACT Â This research studies the effects of compost fertilizer on the growth of red jabon (Anthocepalus macrophyllus) seedling. The method used is completely randomized design, with 5 treatments and 5 replications. No (zero) compost was applied on treatment A as a control, 25 grams of compost on treatment B, 50 grams of compost on treatment C, 75 grams of compost on treatment D, and 100 grams of compost on treatment E. Based on recommendation, growth media used in this research was a mix of soil and sand, with a ratio of 3:2. Variables observed were increase in plant height, increase in stem diameter, increase in number of leaves, and the dry weight of shoot. Results showed that the application of compost fertilizer to red jabon seedling made significant differences in the increase of plant height and stem diameter. Key words: red jabon seedling (Anthocephalus macrophyllus) compost fertilizerÂ  zeorganik